2020
DOI: 10.1111/aor.13747
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mechanical circulatory support on pediatric heart transplant candidates with elevated pulmonary vascular resistance

Abstract: With the new era of increasing use of mechanical circulatory support (MCS) in children, seemingly more patients with elevated pulmonary vascular resistance (PVR) are having positive outcomes. The purpose of this study was to define the effect of MCS on pediatric patients listed for heart transplant with an elevated PVR. The United Network for Organ Sharing (UNOS) database was used to identify patients aged 0‐18 at the time of listing for heart transplant between 2010 and 2019 who had PVR documented (n = 2081).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Evolution of mechanical circulatory support strategies, donor selection, and posttransplant management has helped to mitigate some of the risks associated with elevated PVR. 52 , 53 , 54 Therefore, although elevated PVR may identify higher risk patients, it may not be prohibitive to HTx in the current era.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of mechanical circulatory support strategies, donor selection, and posttransplant management has helped to mitigate some of the risks associated with elevated PVR. 52 , 53 , 54 Therefore, although elevated PVR may identify higher risk patients, it may not be prohibitive to HTx in the current era.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from children awaiting heart transplant show that those with an PVRI >6 W.U. m 2 had better waitlist outcomes when placed on MCS compared to those who were not [109][110][111][112], leading long-term MCS implantation to be considered in advanced stages of the disease as a bridge to HT by improving haemodynamics and reducing post-capillary PH. Figure 5 shows the management of paediatric RCM base on right heart catheterization [5].…”
Section: When Should I Refer Patients For Cardiac Hemodynamic Mechani...mentioning
confidence: 99%
“…19 Thangappan et al . 21 showed that children with PVRs in three categories (<3, 3–6, and >6) had improved survival to transplant or recovery when a VAD was used versus children without VAD support and outcomes were similar amongst the three PVR categories. This suggests that there is a decrease in PVR and positive outcome with the use of VAD alone.…”
Section: Introductionmentioning
confidence: 96%
“…20 The most common causes of mortality include multisystem organ failure (27.5% of all mortalities), neurologic injury (20.3%), and Gastrointestinal (GI) failure (16.3%), followed by circulatory failure (15.7%). 19 Thangappan et al 21 showed that children with PVRs in three categories (<3, 3-6, and >6) had improved survival to transplant or recovery when a VAD was used versus children without VAD support and outcomes were similar amongst the three PVR categories. This suggests that there is a decrease in PVR and positive outcome with the use of VAD alone.…”
Section: Introductionmentioning
confidence: 99%